24 Stroke Risk Factors, Aetiology, and Outcomes in a Multi-ethnic Irish Stroke Population. (16th September 2019) - Finnegan, John; Mello, Sarah; Greene, Suzanne; Cogan, Nicola; Ryan, Dan; Coughlan, Tara; Kennelly, Sean; O'Neill, Des; Mahon, James; Collins, Ronan
Abstract: Background: Stroke aetiology, risk factors and outcomes vary among ethnic groups. The profile of patients presenting to hospital with stroke in Ireland is changing as immigration increases. We aim to describe differences that exist between a multi-ethnic immigrant population and native Irish residents. Methods: Using our hospital's stroke registry we identified all non-Irish (NI) patients admitted to the stroke unit over a two year period through surname recognition (N=44). Country of birth was confirmed by a chart review. The Irish patients admitted over the same time frame were used as a comparison group (N=437). Data was collected on stroke subtype and outcomes, comorbidities, and socioeconomic factors. Patients were grouped based on ethnicity and stroke subtype. Chi squared test was used to analyze the relationship between groups. Results: NI patients made up 9.1% of all stroke unit admissions. NI patients were younger than Irish patients (average age 57.5 vs 69.6 years, p <0.01) and there was a higher prevalence of ICH in the NI group (34.1% vs 11.7%, p <0.01). Hypertension was the most common vascular risk factor in both groups (72.7% vs 68.2%, p = 0.54). Mortality and morbidity was lower in the NI group, with more patients being discharged to home. Conclusion: Our study demonstrates that NI stroke patients have a different risk factor and stroke sub-type profile compared to Irish patients. NI patients are more likely to be young, hypertensive, male, and have higher rates of ICH. Cultural and linguistic barriers may adversely influence health seeking behaviour in this group. These findings underscore the need to identify the root causes of these ethnic differences so targeted primary prevention campaigns can be established.